Impact of an experimental PRRSV and Streptococcus suis coinfection on the pharmacokinetics of ceftiofur hydrochloride after intramuscular injection in pigs1. Issue 5 (16th February 2015) - Day, D. N.; Sparks, J. W.; Karriker, L. A.; Stalder, K. J.; Wulf, L. W.; Zhang, J.; Kinyon, J. M.; Stock, M. L.; Gehring, R.; Wang, C.; Ellingson, J.; Coetzee, J. F.
<x xml:space="preserve">Abstract</x> This study determined the impact of porcine reproductive and respiratory syndrome virus (PRRSV) and Streptococcus suis coinfection on the pharmacokinetic (PK) profile of ceftiofur hydrochloride in pigs after intramuscular (i.m.) injection. Eighteen clinically normal crossbred gilts were assigned by weight into a challenge group (10 pigs) and control group (eight pigs). Pigs in both groups received a single i.m. injection of ceftiofur hydrochloride (Excenel RTU Sterile Suspension; Zoetis) at a 5 mg/kg BW dose. Serial blood samples were collected to characterize the plasma concentration curve. After a 10 days drug washout period, the challenge group was inoculated with 2 mL of PRRSV isolate VR‐2385 (105.75 50% tissue culture infective doses per mL) intranasally and 8 days later inoculated S. suis. When clinical disease was evident, the second PK assessment began in both challenge and control groups. Coinfected pigs demonstrated lower values of AUC and CMAX, but higher values of Cl/F and Vz/F indicating drug kinetics were altered by infection. The data from this study have implications on ceftiofur treatment regimens in diseased pigs.